Reciprocal activating interaction between dendritic cells and aminobiphosphonates-stimulated T cells: role of CD86 and inflammatory cytokines (Hematology Meeting Reports, 2009)
ognate interactions are a common feature of the acquired immune response, where intimate cell contacts govern critical events such as Ag presentation and delivery of T cell help to CTLs and B cells, while the coordinated control of innate immunity is mostly mediated by cytokine loops. However, a number of studies recently highlighted the importance of DC interactions with NK cells, an important effector cell type of innate immunity, in the regulation of DC maturation.1,2,3